ANALYSIS OF REVENUE SHARING FUND (DBH) REALIZATION IN DELI SERDANG REGENCY FISCAL YEAR 2024 - Fahrezy, Sultan; Tampubolon, Deaz Perdinan; Muda, Iskandar (JIAR : Journal Of International Accounting Research, 2025)
This study examines the realization of the Revenue Sharing Fund (Dana Bagi Hasil/DBH) in Deli Serdang Regency for the fiscal year 2024. The DBH is one of the central government’s fiscal transfer instruments that plays a significant role in supporting local budgets, particularly in regions with limited revenue capacity. The main objec tive of this paper is to analyze the types of DBH received, the compa rison between budget allocation and realization, and the implications for regional fiscal management. Data were collected from official fin ancial reports of the Regency Government and analyzed using a desc riptive approach. The findings indicate that the total DBH allocation for Deli Serdang in 2024 reached IDR 2,527.59 billion, with realizati on amounting to IDR 2,499.97 billion or 98.91%. Almost all compon ents, including tax-based DBH (PPh, PBB, and excise) and natural resource-based DBH (oil, gas, forestry, mining, geothermal, and fisheries), recorded realization rates close to 100%. This high level of realization reflects the effectiveness of the transfer mechanism fro m the central to the regional government. Nevertheless, the strong rel iance on DBH suggests a need to strengthen its own-source revenue in order to achieve greater fiscal independence in the future.